On Desert Shores : Archaeology and History of the Western Midriff Islands in the Gulf of California - Bowen, Thomas, 1942- (Book collections on Project MUSE., 2022)
"This project represents the first archaeological research ever conducted on the Western Midriff Islands, located midway in the Gulf of California, Mexico. It is also the first attempted compilation of the historic record for the islands, including information on the Seri people of Sonora and the now extinct Cochimís people of Baja California. There is also a strong natural history component to the project since much of the historic exploration of the islands, both Euroamerican and Mexican, was biological in nature. This results in a current evaluation of the environmental impacts on the islands and the conservation approaches that have been undertaken"--